Therapeutic efficacy of n-Docosanol against velogenic Newcastle disease virus infection in domestic chickens - Orabi, Ahmed; Hussein, Ashraf; Saleh, Ayman A.; Megahed, Ayman M.; Metwally, Mohamed; Moeini, Hassan; Metwally, Aya Sh. (Frontiers in Microbiology, 2022)
The control of Newcastle disease virus (NDV) infection depends solely on vaccination which in most cases is not sufficient to restrain the consequences of such a highly evolving viral disease. Finding out substances for preparing an efficient anti-ND drug would be of high value. n-Docosanol is a saturated fatty alcohol with an inhibitory effect against many enveloped viruses. In this study, we evaluated the therapeutic effect of n-docosanol on NDV infection and shedding in chickens. To this end, chickens infected with a highly virulent NDV were treated with low to high concentrations of n-docosanol (20, 40, and 60 mg/kg body weight) for 4-successive days, once they showed the disease symptoms. Symptoms development was found to discontinue 24-72 hours post-treatment. The survival rate in the NDV-infected chickens raised 37.4–53.2% after the treatment. n-Docosanol treatment was also found to significantly reduce virus load in the digestive (26.2-33.9%), respiratory (38.3-63%), nervous (26.7-51.1%), and lymphatic (16.4-29.1%) tissues. Histopathological scoring of NDV lesions revealed prominent rescue effects on the histology of different tissues. Importantly, n-docosanol treatment significantly reduced virus shedding in oropharyngeal discharge and feces thereby allowing the restriction of NDV spread. Altogether, our findings suggest n-docosanol as a promising remedy in the control strategy of Newcastle disease in the poultry industry.